Segregation Versus Colocalization: Orthogonally Functionalized Binary Micropatterned Substrates Regulate the Molecular Distribution in Focal Adhesions. (15th May 2015) - Guasch, Judith; Conings, Bert; Neubauer, Stefanie; Rechenmacher, Florian; Ende, Karen; Rolli, Claudio G.; Kappel, Christian; Schaufler, Viktoria; Micoulet, Alexandre; Kessler, Horst; Boyen, Hans‐Gerd; Cavalcanti‐Adam, Elisabetta Ada; et al.
<x xml:space="preserve">Abstract</x> Orthogonally functionalized binary micropatterned substrates are produced using a novel protocol. The use of adequate peptido‐mimetics enables an unprecedented segregation of purified αvβ3 and α5β1 integrins in adjacent microislands and evidences the preference of U2OS cells to colocalize such receptors. Moreover, this tendency can be altered by varying the geometry and composition of the micropatterns.